THE VALUE OF ONLINE LEARNING: PERSPECTIVES FROM THE UNIVERSITY OF ILLINOIS AT SPRINGFIELD - Oakley, Burks (Online Learning, 2004)
The value of online learning is analyzed from the perspective of the University of Illinois at Springfield (UIS). The first type of value (merit, worth) of online learning is discussed, with the conclusion that online learning is of significant value to various constituencies, including students, faculty, the institution, and society. A second type of value (cost-benefit) of online learning is analyzed and seen to be outstanding at UIS, compared to other online alternatives. Finally, the two types of value of online learning are related to the Sloan-C quality pillars.